Evolutionarily Conserved Histone Methylation Dynamics during Seed Life-Cycle Transitions - Müller, Kerstin (Public Library of Science, 2012)
Plants have a remarkable ability to react to seasonal changes by synchronizing life-cycle transitions with environmental conditions. We addressed the question of how transcriptional re-programming occurs in response to an environmental cue that triggers the major life cycle transition from seed dormancy to germination and seedling growth. We elucidated an important mechanistic aspect of this process by following the chromatin dynamics of key regulatory genes with a focus on the two antagonistic marks, H3K4me3 and H3K27me3. Histone methylation patterns of major dormancy regulators changed during the transition to germination and seedling growth. We observed a switch from H3K4me3 and high transcription levels to silencing by the repressive H3K27me3 mark when dormancy was broken through exposure to moist chilling, underscoring that a functional PRC2 complex is necessary for this transition. Moreover, this reciprocal regulation by H3K4me3 and H3K27me3 is evolutionarily conserved from gymnosperms to angiosperms.